For a certain arithmetic sequence, the sum of the first 1 0 0 terms is S 1 0 0 = 1 6 5 5 0 , and the sum of the first 1 0 0 sums ( S 1 + S 2 + … S 1 0 0 ) is T 1 0 0 = 5 8 5 8 0 0 .
Find the first term of the sequence.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! I solved it the same way.
Let a = first term and d = common difference. Let S k = the sum of the first k terms. Given that S 100 = 16550, we have that 16550 = (100/2) (a + a + 99d) = 100a + 4950d. Now, the sum from S_1 to S_100= 585800, where S_k = ka + [k(k - 1)/2] d. Forming the sum, 585800 = 5050a + 166650d. We have 2 simultaneous equations for a and d. Eliminating d, we have a = 17.
For T(n) = a+d(n-1), we were taught that sum formulation of S(n) = n(a+l)/2 = (n/2)[2a+d(n-1)], but sum of sum and so on are just an extension of the previous summations. Here, sum of S(n), T in this question, but let's call it R(n), equals R(n) = (n/2)((n+1)/3)[3a+d(n-1)], and sum of R(n) is Q(n) = (n/2)((n+1)/3)((n+2)/4)[4a+d(n-1)]. Just add another factor of n, plus an extra one both for nominator AND denominator, and change the coefficient of a to match the number of n factors (the same as the number of brackets in the formula).
T(100) = 100*101(3a+99d)/6.
and.
S(100) = 100(2a+99d)/2, we get a = 17.
Similar to Pi Han Goh's solution:
∑ i = 0 9 9 ( a i + b ) = 1 6 5 5 0 ∧ ∑ j = 0 9 9 ( ∑ i = 0 j ( a i + b ) ) = 5 8 5 8 0 0 ⇒ a → 3 , b → 1 7 . Since the first term is just b , as i = 0 , the answer is 1 7 .
Problem Loading...
Note Loading...
Set Loading...
Let a and d denote the first term and the common difference of this arithmetic sequence.
The sum of the first n terms of this sequence is given by S n = 2 n ( 2 a + ( n − 1 ) d ) .
We are given that S 1 0 0 = 1 6 5 5 0 , thus 2 1 0 0 ( 2 a + 9 9 d ) = 1 6 5 5 0 ⇔ 2 a + 9 9 d = 3 3 1 .
And we are also given that S 1 + S 2 + ⋯ + S 1 0 0 = 5 8 5 8 0 0 . Thus, k = 1 ∑ 1 0 0 [ 2 k ( 2 a + ( k − 1 ) d ) ] 2 a ( k = 1 ∑ 1 0 0 k ) + d ( k = 1 ∑ 1 0 0 ( k 2 − k ) ) = = 5 8 5 8 0 0 5 8 5 8 0 0 ⋅ 2
Using the algebraic identities, k = 1 ∑ n k = 2 n ( n + 1 ) and k = 1 ∑ n k 2 = 6 n ( n + 1 ) ( 2 n + 1 ) , the equation above simplifies to 1 0 1 a + 3 3 3 3 d = 1 1 7 1 6 .
Solving these 2 linear equations simultaneously gives a = 1 7 , d = 3 .